Analisis Manajemen Piutang dalam Meningkatkan Likuiditas Perusahaan - Wilda Ningsih; Haidar Hafizh Alramdhani; Arif Maulana; Fajrin Ramadhani; Ning Tyas Arlita; Najha Khairotunnisa; Mukhlishotul Jannah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of receivables management on improving corporate liquidity, focusing on credit policies, collection procedures, and the integration of Islamic economic principles. The background of this research is based on the phenomenon of cash flow gap that often occurs in Indonesian companies, where poorly managed trade receivables cause company funds to be trapped for long periods, threatening liquidity stability even though the profits generated are positive. The research method used is a descriptive quantitative approach with a causal-comparative design, using secondary data in the form of audited annual financial statements. Data collection techniques include documentation studies, literature reviews, and structured interviews (optional), with the population consisting of company financial statements since operations began, and samples taken through purposive sampling based on specific criteria. The results show that effective receivables management through the implementation of strict credit standards based on 5C analysis (Character, Capacity, Capital, Collateral, Condition), monitoring of aging schedules, and digitization of collection systems positively contributes to accelerating receivable turnover and reducing Days Sales Outstanding (DSO). From the Islamic economic perspective, the implementation of DSN-MUI Fatwa No. 17 regarding sanctions (Ta'zir) for capable customers who delay payments proves effective in creating debtor discipline without violating anti-usury principles, thereby smoothing cash inflow. In conclusion, there is a positive and significant relationship between receivable turnover and liquidity as measured by Current Ratio and Quick Ratio, while DSO is inversely related to liquidity. This study recommends that companies balance credit policies with liquidity capacity, adopt automated collection technology, and for Islamic institutions, socialize ethical sanctions as financial discipline education.